2020
DOI: 10.1177/0956797620903113
|View full text |Cite
|
Sign up to set email alerts
|

Bilingualism Affords No General Cognitive Advantages: A Population Study of Executive Function in 11,000 People

Abstract: Whether acquiring a second language affords any general advantages to executive function has been a matter of fierce scientific debate for decades. If being bilingual does have benefits over and above the broader social, employment, and lifestyle gains that are available to speakers of a second language, then it should manifest as a cognitive advantage in the general population of bilinguals. We assessed 11,041 participants on a broad battery of 12 executive tasks whose functional and neural properties have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
82
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(92 citation statements)
references
References 45 publications
1
82
0
2
Order By: Relevance
“…Recently, psychologists have questioned whether bilingualism has any effect on higher-level cognition, positive or negative [7][8][9]. In this paper we present a novel behavioral experiment analyzed using Bayesian hypothesis testing and find support for no relation between bilingualism and creativity.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…Recently, psychologists have questioned whether bilingualism has any effect on higher-level cognition, positive or negative [7][8][9]. In this paper we present a novel behavioral experiment analyzed using Bayesian hypothesis testing and find support for no relation between bilingualism and creativity.…”
Section: Introductionmentioning
confidence: 73%
“…Finally, it is worth noting that there is growing skepticism in the bilingual literature about the existence of bilingual advantages [7][8][9]. For example, Paap, Johnson, and Sawi (2015) concluded that the proposed bilingual advantages for executive function do not exist, and that studies that demonstrate these advantages fail to match participants on demographics, have small sample sizes, or have low reproducibility [7].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…The arguments for no bilingual effects on neurocognition are predicated on the notion that if any adaptations (or 'advantages') do stem from bilingualism, then they should be robust across all groups and types of bilinguals when compared to monolingual controls (see e.g. Nichols, Wild, Stojanoski, Battista, & Owen, 2020). However, this line of argument is flawed.…”
Section: Introductionmentioning
confidence: 99%
“…They also emphasized the need for pre-registration of studies to ensure that negative or null-findings are published, too. Similarly, a large-scale study containing data from 11,000 participants found no conclusive evidence of bilinguals outperforming monolinguals [ 58 ]. It is important to point out, however, that individual differences in bilingual experiences were not taken into account in these larger reviews.…”
Section: Introductionmentioning
confidence: 99%